Is there addiction to loud music? Findings in a group of non-professional pop/rock musicians - Schmuziger, Nicolas (Audiol Res, 2012)
Listening to loud music may be connected to addictive behavior possibly leading to damaging effects on the cochlea. We hypothesized that members of non-professional pop/rock bands with regular exposure to loud music are more likely to show an addictive-like behavior for loud music than matched control subjects. Fifty non-professional musicians and 50 matched control subjects were asked to complete the Northeastern Music Listening Survey (NEMLS) with two basic components. The first comprises an adaptation of the validated Michigan Alcohol Screening Test (MAST) to study the addictive-like behavior towards loud music. The second comprises the criteria outlined by the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) of the American Psychiatric Society for the diagnosis of substance dependence. The NEMLS was scored using the same point system as used in the MAST. The DSM-IV criteria for substance dependence were met by nine of the musician group and by one control subject. Seven of these nine musicians also had a positive NEMLS score. Traits of addictive-like behavior to loud music were detected more often in members of nonprofessional pop/rock bands than in control subjects.